Correlation between Physical Activity and Cardiovascular Endurance of the Employees in Universitas Swadaya Gunung Jati, Cirebon, Indonesia - Agestri, Salsabila Carissa Arsyana; Sriwiyati, Kati; Syah, Pangeran Akbar (GHMJ (Global Health Management Journal), 2024)
Background: Cardiovascular endurance refers to a person's ability to perform activities involving the entire body at moderate to high intensity over extended periods. Cardiovascular endurance is influenced by several factors, such as physical activity. Moderate to high-intensity physical activity trains the body to exchange oxygen more efficiently and results in enhancing cardiovascular endurance. Other factors that could contribute in cardiovascular endurance are smoking and Body Mass Index (BMI). Aims: To find the correlation between physical activity, BMI, smoking, and cardiovascular endurance among employees of Universitas Swadaya Gunung Jati, Cirebon, Indonesia. Methods: It was an analytic observational study with a cross-sectional approach that used the GPAQ physical activity questionnaire and cardiovascular endurance data that was obtained through the Harvard Step Test involving 77 educational staff employees at Universitas Swadaya Gunung Jati. The analytical statistics used was Spearman’s correlation test with a significance value of p = <0.05. Results: Most of the Universitas Swadaya Gunung Jati employee’s had moderate level of physical activity (44.2%) and very low cardiovascular endurance (37.7%). The analytical statistic showed a significant correlation between physical activity and cardiovascular endurance with a p-value of 0.034 and a Spearman's r of 0.242. Smoking has significant correlation with cardiovascular endurance with p value of 0.003 and Spearman’s r of 0.338. BMI showed negative and weak correlation with cardiovascular endurance with p value 0.008 and Spearman’s r -0.302. Conclusion: There was a significant correlation between physical activity and cardiovascular endurance among the employees of Universitas Swadaya Gunung Jati, Cirebon, Indonesia.   Received: 25 September 2024  |  Reviewed: 26 October 2024  |  Revised: 17 November 2024  |  Accepted: 30 November 2024.